Decentralized controller design for boiler system - Ma, Liyu (2008)
Boiler control systems are typical nonlinear, multivariable control systems. In this dissertation a novel auto-tuning technique for the boiler-turbine system is presented. At first a three-input three-output (TITO) boiler-turbine model was identified by using closed-loop parameter identification method in frequency domain. Based on simple sequential step tests, the coupled closed-loop system is decoupled equivalently into nine independent single open-loop processes.